Lifetime Suicidal Behaviors and Career Characteristics Among U.S. Army Soldiers: Results from the Army Study to Assess Risk and Resilience in Servicemembers (Army STARRS). Issue 2 (20th June 2017) - Millner, Alexander J.; Ursano, Robert J.; Hwang, Irving; King, Andrew J.; Naifeh, James A.; Sampson, Nancy A.; Zaslavsky, Alan M.; Stein, Murray B.; Kessler, Ronald C.; Nock, Matthew K.
Abstract : The current report presents data on lifetime prevalence of suicide ideation and nonfatal attempts as reported by the large representative sample of U.S. Army soldiers who participated in the Consolidated All‐Army Survey of the Army Study to Assess Risk and Resilience in Servicemembers ( N  =   29, 982). We also examine associations of key Army career characteristics with these outcomes. Prevalence estimates for lifetime suicide ideation are 12.7% among men and 20.1% among women, and for lifetime suicide attempts are 2.5% and 5.1%, respectively. Retrospective age‐of‐onset reports suggest that 53.4%–70% of these outcomes had preenlistment onsets. Results revealed that, for both men and women, being in the Regular Army, compared with being in the National Guard or Army Reserve, and being in an enlisted rank, compared with being an officer, is associated with increased risk of suicidal behaviors and that this elevated risk is present both before and after joining the Army.